Dose escalation and expansion phase I studies with the tumour-targeting antibody-tumour necrosis factor fusion protein L19TNF plus doxorubicin in patients with advanced tumours, including sarcomas. (June 2021) - Schliemann, Christoph; Hemmerle, Teresa; Berdel, Andrew F.; Angenendt, Linus; Kerkhoff, Andrea; Hering, Jan P.; Heindel, Walter; Hartmann, Wolfgang; Wardelmann, Eva; Chawla, Sant P.; de Braud, Filippo; Lenz, Georg; et al.
Abstract: Background: L19TNF is a recombinant fusion protein composed of a human antibody fragment and human tumour necrosis factor. L19TNF targets the EDB domain of oncofetal fibronectin highly expressed in tumour vasculature and induces tumour remission in mouse tumours. We summarise two phase I trials testing a combination of L19TNF with doxorubicin in patients with solid tumours, particularly soft tissue sarcomas (STS). Patients and methods: The first study, an open-label, dose-escalation and expansion phase I study of L19TNF plus doxorubicin, enrolled 27 patients. Three cohorts (10.4–17 μg/kg L19TNF) of patients received L19TNF intravenously at days 1, 3, and 5 and doxorubicin (75 mg/m 2, then 60 mg/m 2 ) on day 1 every 3 weeks. The expansion cohort enrolled patients with STS. The second study tried to re-escalate the doxorubicin dose to 75 mg/m 2 with 13 μg/kg L19TNF. Among primary objectives was the establishment of a recommended dose (RD). Results: The combination was safely applicable. Dose-limiting toxicity occurred either at 17 μg/kg L19TNF or at 75 mg/m 2 doxorubicin. RD is 13 μg/kg L19TNF plus 60 mg/m 2 doxorubicin. In 15 STS patients of the extension cohort evaluable for efficacy, antitumour activity was observed with complete remission in 1, partial remission in 1 and minor tumour shrinkage in 7 patients. The median overall survival for this heavily pretreated cohort was 14.9 months. Conclusion: L19TNF can be safely applied in combination with doxorubicin and induces encouraging tumour remissions in patients with soft tissue sarcomas. Highlights: This phase I trial studied L19TNF targeted to tumour vasculature plus doxorubicin. Primary objective was to find a recommended dose (RD) for further trials. RD is 13 μg/kg L19TNF (days 1, 3, 5 of a cycle) plus 60 mg/m 2 doxorubicin (day 1). The combination showed encouraging activity against soft tissue sarcomas (STS). The regimen is now tested in two multicenter randomised trials for patients with STS.